Women Empowerment in Livestock Index (WELI) - CGIAR Research Program on Livestock (2019)
The tool is being used by other partners. It is suitable for use by anyone (including scientists, researchers, development practitioners) who is interested in measuring the empowerment of women in livestock systems, and the impact on women's empowerment of a given intervention.